2020
DOI: 10.1186/s13195-020-00634-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma transferrin and hemopexin are associated with altered Aβ uptake and cognitive decline in Alzheimer’s disease pathology

Abstract: Background: Heme and iron homeostasis is perturbed in Alzheimer's disease (AD); therefore, the aim of the study was to examine the levels and association of heme with iron-binding plasma proteins in cognitively normal (CN), mild cognitive impairment (MCI), and AD individuals from the Australian Imaging, Biomarker and Lifestyle Flagship Study of Ageing (AIBL) and Kerr Anglican Retirement Village Initiative in Ageing Health (KARVIAH) cohorts. Methods: Non-targeted proteomic analysis by high-resolution mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 81 publications
1
20
2
Order By: Relevance
“…Moreover, CSF Hb subunits were significantly higher in MCI-c compared to MCI-nc and were associated with decreased CSF Aβ and increased CSF ptau. The present CSF study extends our recent plasma study (Ashraf et al, 2020a), and solidifies evidence for the involvement of heme/iron dyshomeostasis in the pathogenesis of AD.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, CSF Hb subunits were significantly higher in MCI-c compared to MCI-nc and were associated with decreased CSF Aβ and increased CSF ptau. The present CSF study extends our recent plasma study (Ashraf et al, 2020a), and solidifies evidence for the involvement of heme/iron dyshomeostasis in the pathogenesis of AD.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the association of low CSF HPX levels with low CSF Aβ, high CSF ptau, increased glucose hypometabolism and cognitive decline, i.e., disease progression (although not MCI conversion to AD). In our previous study (Ashraf et al, 2020a), plasma HPX was associated with brain amyloid deposition, albeit from a different cohort. HPX is an abundant plasma protein that is also expressed by both neurons and glia (Morris et al, 1993), with the majority of CSF HPX produced intrathecally in normal human subjects (Garland et al, 2016).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Emerging evidence suggested that blood iron homeostasis is altered in AD and already in MCI (Faux et al, 2014 ; Ashraf et al, 2020 ; Guan et al, 2020 ), including systemic variation of markers of iron metabolism, such as transferrin saturation and ceruloplasmin/transferrin ratio in serum (Squitti et al, 2010 ). Interestingly, in our case, we found a negative correlation between t-Tau and Tf in serum in AD that can support a role of Tf in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%